2018
DOI: 10.1128/aac.01824-17
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Cycloserine Efficacy in Treatment of Multidrug-Resistant and Extensively Drug-Resistant Tuberculosis in Beijing, China

Abstract: Cycloserine (Cs) is recommended by the World Health Organization as a second-line drug to treat multidrug-resistant tuberculosis (MDR-TB); however, its efficacy has never been sufficiently evaluated. To gain some insights into the value of cycloserine for MDR-TB treatment, bacteriostatic effect was determined and patient validations were performed prospectively. The activity of Cs against 104 wild-type strains was determined, and serum Cs concentrations were measured for 73 MDR TB patients 2 h after administra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…A possible explanation for this finding is that treatment of MDR-TB includes multiple drugs, and an observational study without strict placebo controls hardly assesses the efficacy of a single agent. Furthermore, a recent study has shown that more than half of patients with the recommended dosage of 10 mg/kg of cycloserine prescription had peak serum concentrations lower than the minimum inhibitory concentrations of the strains isolated from the corresponding patients, suggesting the need for adjusting each patient’s dosages depending on the clinical pharmacokinetic and pharmacodynamic assessments 24,25…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this finding is that treatment of MDR-TB includes multiple drugs, and an observational study without strict placebo controls hardly assesses the efficacy of a single agent. Furthermore, a recent study has shown that more than half of patients with the recommended dosage of 10 mg/kg of cycloserine prescription had peak serum concentrations lower than the minimum inhibitory concentrations of the strains isolated from the corresponding patients, suggesting the need for adjusting each patient’s dosages depending on the clinical pharmacokinetic and pharmacodynamic assessments 24,25…”
Section: Discussionmentioning
confidence: 99%
“…Despite exhibiting promising safety, we found that the administration of CS produces a higher proportion of serious ADRs resulting in discontinuation of CS. In addition, low plasma concentration is another important concern for the clinical application of CS 24,25. Although the increased dosage of CS could overcome this obstacle, it may also pose a higher safety risk.…”
Section: Discussionmentioning
confidence: 99%
“…PZA was always controversial in the treatment of MDR-TB and XDR-TB, some studies showed that PZA resistant or not did not impact its anti-microbial activity (21,26,27), however, the high resistant rate of PZA had been considered its application in the future (28). In the present study, we tested PZA resistance by MIC value, the resistance rate was 50.9%.…”
Section: Discussionmentioning
confidence: 83%
“…The other drugs made up the regimen, Cs had low resistant rate and Cs containing regimen can achieve a highly successful outcome (66% of cure rate) in China reported by one study (19) and 69.4% of treatment success rate in another study (20). MIC for 90% of the recruited stains were below 32 µg/ml (21). Above studies demonstrated the slight side effects of Cs in the treatment of MDR-TB,the present study also veri ed its safety and e cacy.…”
Section: Discussionmentioning
confidence: 95%